2019
DOI: 10.7567/1882-0786/ab4b7b
|View full text |Cite
|
Sign up to set email alerts
|

Single- and dual-wavelength switchable mode-locked dissipative soliton Yb-doped fiber laser based on graphene/WS2 nanocomposites modelocker and polarization controller

Abstract: We report a single- and dual-wavelength switchable mode-locked dissipative soliton in an ytterbium-doped fiber laser based on graphene/WS2 nanocomposites saturable absorber. The graphene/WS2 nanocomposites film possesses efficient saturable absorption characteristics with large modulation depth (45.1%), which results in the stable single-wavelength mode-locking operation with pulse duration of 450 ps. By carefully rotating the polarization controller, the mode-locking operation can be switched to a dual-wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…reported that graphene/tungsten disulfide (graphene/WS 2 ) produced by LPE had unique properties which graphene and WS 2 did not have. [ 78 ] In 2021, Xia et al. found that the heterostructure could enhance the stability of the SA material.…”
Section: Fabrication Of Heterostructure Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that graphene/tungsten disulfide (graphene/WS 2 ) produced by LPE had unique properties which graphene and WS 2 did not have. [ 78 ] In 2021, Xia et al. found that the heterostructure could enhance the stability of the SA material.…”
Section: Fabrication Of Heterostructure Materialsmentioning
confidence: 99%
“…[74] In 2019, Ma et al reported that graphene/tungsten disulfide (graphene/ WS 2 ) produced by LPE had unique properties which graphene and WS 2 did not have. [78] In 2021, Xia et al found that the heterostructure could enhance the stability of the SA material. They generated black phosphorus/titanium carbide (BP/ Ti 3 C 2 ) powder and found that the properties remained stable for weeks.…”
Section: Liquid Phase Exfoliationmentioning
confidence: 99%
See 1 more Smart Citation
“…223 Further experiments showed that the passively mode-locked EDFL by using the SnS 2 SA with a thickness of 108.7 nm has the best output characteristic in achieving ultra-short pulses (with pulse duration of 132.9 fs at 1561 nm). Heterostructure/composite nanostructures such as graphene-WS 2 , 224,266,267 MoS 2 -WS 2 , 268 WS 2 -MoS 2 -WS 2 , 269 MoS 2 -Sb 2 Te 3 -MoS 2 , 270 MoS 2 -SiO 2 , 271 and TaS 2 -SiO 2 272 were also used as the SA material for applications in passively mode-locked fiber lasers. In addition, a passively mode-locking fiber laser with TMDC-based SA was also observed due to the sub-band gap absorption.…”
Section: Applications Of Emerging Nanostructured Materials As the Sas...mentioning
confidence: 99%
“…In 2019, Ma et al took a leap forward in the field of multiwavelength fiber laser. [131] With the help of graphene/WS 2 [128] Copyright 2013, IOP Publishing Ltd. nanocomposite, they managed to realize a YDFL that was able to switch the dissipative soliton's central wavelength between a single wavelength at 1066.2 nm and a dual-wavelength at both 1066.4 and 1069.2 nm. They successfully achieved a pulse duration of 450 ps and a repetition rate up to 19.68 GHz from a stable mode-locked operation with a single-wavelength at 1066.2 nm.…”
Section: Graphenementioning
confidence: 99%